KONSEP MANUSIA DALAM SISTEM PENDIDIKAN ISLAM - Dinasril Amir (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
Education concept closely relates to humans’ concept themselves. How humans’ concept will relate to their concept on education because the education itself is an effort to direct humans’ concept. Islamic concept on education is a holistic unit. This paper describes the humans’ concept that has dignity, well in nature, multidimentional, and multipotential. Thus, the Islamic education attempts to direct students become self-confidence, creative and innovative in developing their capabilities. New education system in Islam is determined by new concept on Islamic thinking.